SHOCK ABSORBER - YAMASHITA Mikio (2025)
The shock absorber is provided with a first passage through which a working fluid flows out from a chamber on an upstream side to a chamber on a downstream side due to movement of a piston, a first damping force generation mechanism that is provided in the first passage and that generates damping force, a second passage that is provided separately from the first passage, a second damping force generation mechanism that is provided in the second passage and that generates damping force, and a volume variable mechanism that changes the volume of a volume chamber provided in parallel with the second passage. The second damping force generation mechanism generates a first resistance force from a frequency at which the piston frequency is lower than a first frequency. The variable volume mechanism is provided with a resistance force generation mechanism that limits the flow rate of the working fluid to the second damping force generating mechanism when the piston frequency becomes equal to or higher than the first frequency, and generates a second resistance force when the piston frequency becomes equal to or higher than the first frequency. La présente invention concerne un amortisseur pourvu d'un premier passage à travers lequel un fluide de travail s'écoule hors d'une chambre sur un côté amont vers une chambre sur un côté aval en raison du mouvement d'un piston, d'un premier mécanisme de génération de force d'amortissement qui est disposé dans le premier passage et qui génère une force d'amortissement, d'un second passage qui est disposé séparément du premier passage, d'un second mécanisme de génération de force d'amortissement qui est disposé dans le second passage et qui génère une force d'amortissement, et d'un mécanisme à volume variable qui change le volume d'une chambre de volume disposée en parallèle avec le second passage. Le second mécanisme de génération de force d'amortissement génère une première force de résistance à partir d'une fréquence à laquelle la fréquence de piston est inférieure à une première fréquence. Le mécanisme à volume variable est pourvu d'un mécanisme de génération de force de résistance qui limite le débit du fluide de travail au second mécanisme de génération de force d'amortissement lorsque la fréquence de piston devient égale ou supérieure à la première fréquence, et génère une seconde force de résistance lorsque la fréquence de piston devient égale ou supérieure à la première fréquence. この緩衝器は、ピストンの移動により上流側となる室から下流側となる室に作動流体が流れ出す第１通路と；前記第１通路に設けられ、減衰力を発生する第１減衰力発生機構と；前記第１通路とは別に設けられる第２通路と；前記第２通路に設けられ、減衰力を発生する第２減衰力発生機構と；前記第２通路とは並列に設けられた体積室の体積を変更する体積可変機構と；を有する。そして、前記第２減衰力発生機構は、ピストン周波数が第１の周波数よりも低い周波数から第１の抵抗力を発生する。また、前記体積可変機構は、前記ピストン周波数が前記第１の周波数以上になると、前記第２減衰力発生機構への前記作動流体の流量を制限し、前記ピストン周波数が前記第１の周波数以上になると、第２の抵抗力を発生する、抵抗力発生機構を備える。